Wideband patch antenna through introducing co‐plane terminal - Boyu Sima; Zhengkun Guo; Run Liu; Heling Gong; Qingqing Yang; Jun Hu; Zhiwei Sun; Wen Wu (IET Microwaves, Antennas & Propagation, 2024)
Abstract Wideband operation is a crucial topic in patch structure research. Various wideband methods have been developed for patch antennas. However, some of the key benefits of patch antennas, such as semi‐space radiation and easy fabrication, are degraded. In this study, we refer to the planar inverted‐F antenna (PIFA) and propose a co‐plane terminal loading strategy, resulting in an antenna model termed the co‐plane terminal loaded antenna (CTLA). It transforms the dipole‐to‐background metallic via in PIFA to a dipole‐to‐feed gap in CTLA. Because the gap is a coupling connection, the impedance‐match and resonant‐frequency performance improve, resulting in a wider bandwidth. Based on the proposed approach, three CTLAs, including an original CTLA, an improved CTLA, and a multi‐path CTLA, were constructed and simulated, with relative bandwidths of 63.5%, 55%, and 62%, respectively. The radiation pattern is typically patch‐like, radiating in semi‐space, and hybrid polarisation over the working band. Finally, the improved and multi‐path CTLAs are fabricated and measured to validate this method and ensure that the results are consistent with the simulation results accurately. This study proposes a terminal‐loading method for patch structures, which results in wideband radiation. It can be used in wideband phased arrays, communication systems etc.